Changing distribution of age, clinical severity, and genotypes of rotavirus gastroenteritis in hospitalized children after the introduction of vaccination: a single center study in Seoul between 2011 and 2014. Issue 1 (December 2016) - Shim, Jung; Chang, Ju; Shin, Sue; Moon, Jin; Ko, Jae
Abstract Background This study aimed to explore changes in clinical epidemiology and genotype distribution and their association among hospitalized children with rotavirus gastroenteritis after the introduction of vaccines. Methods Between November 2010 and October 2014, hospitalized children with acute gastroenteritis were enrolled. Rotavirus genotypes were confirmed through reverse transcription-polymerase chain reaction (RT-PCR), semi-nested PCR, and sequencing. Clinical information including vaccination status and the modified Vesikari scores were collected. Results Among 179 children with rotavirus infection, nineteen (10.6 %) were completely vaccinated. During the study period, the number of children between three and 23 months of age decreased significantly compared to the number of children older than 24 months of age (P  = 0.010), who showed lower diarrhea severity (duration, P  = 0.042; frequency, P  = 0.021) but higher vomiting severity (P  = 0.007, 0.036) compared to the former. Vaccination status was also significantly associated with lower vomiting severity after adjustment for age (frequency only, P  = 0.018). The predominant genotypes were G2P[4] (18.4 %), G1P[8] (14.5 %), and G1P[4]P[8] (12.8 %), and the prevalence of genotypes with uncommon and mixed combinations was more than 50 %. Children infected with G2P[4] strains tended to be older (P  = 0.005) and had more severe vomiting (P  = 0.018, 0.006) than those with G1P[8]. Conclusions Increase in age of infected, hospitalized children was accompanied by change in clinical severity during 2011–2014 after the introduction of vaccines in Seoul. Clinical severity was also associated with vaccination status and genotype. Long-term large scale studies are needed to document the significance of the increase in genotypes of uncommon and mixed combinations.